FROM THE HISTORY OF RELATIONS OF THE KARAKALPAKS WITH THE UZBEKS - Tleumuratova N.M. (International Journal of Innovations in Engineering Research and Technology, 2021)
This article is about the relations study of the Karakalpaks with the Uzbeks and the historiography of Karakalpakstan, taking into consideration of ethnic-cultural relations of Karakalpaks with the neighbor people in the 18th and beginning of the 20th century.